Model Bisnis Klinik POLTRADA sebagai Fasilitas Kesehatan Tingkat Pertama (FKTP) Berbasis Blue Ocean Strategy (BOS) Wilayah Tabanan Bali: indonesia - Reinaldy Yuda Afriza; Sahat Saragi; Lies Putriana (UNIB Press, 2025)
Poltrada Clinic is one of the First Level Health Facilities in Bali that serves 634 ‘BPJS Kesehatan’ participants. The clinic under the Ministry of Transportation has the opportunity to develop its services and business reach along with the development of the number of industries in Tabanan. Therefore, its performance needs to be evaluated to formulate an optimal business strategy. The analysis method uses SWOT analysis followed by the Quantitative Strategic Planning Matrix and Blue Ocean Strategy approaches to obtain the right strategic priorities and business models. Data collection was carried out by interviewing 8 informants. The results of the data analysis show: The SWOT matrix produces (x, y = 0.84; 1.89) where this point is in quadrant I, which means the clinic is in a favorable situation. Based on the CPM results from 7 key factors, Poltrada Clinic has a score of 3.49 which is in the first position compared to 3 existing clinics. This means that Poltrada Clinic has a stronger competitive advantage in various key factors for the success of the health service industry. The results of the QSPM matrix processing show that the highest value lies in alternative strategy 1, namely